A salt tolerant Sphingosinicella microcystinivorans A3 isolated from soil contaminated with mercury in traditional gold mining of Jendi Village, Wonogiri District, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sutami, Purwanto, Rosariastuti R. 2021. A salt tolerant Sphingosinicella microcystinivorans A3 isolated from soil contaminated with mercury in traditional gold mining of Jendi Village, Wonogiri District, Indonesia. Biodiversitas 22: 3785-3791. Isolation and characterization of indigenous bacteria from the soil of traditional gold mining contaminated with mercury is the first step in a series of research to explore and utilize indigenous bacteria in Jendi's area. This study was aimed to determine the characteristics and identity of bacterial isolates from soil of traditional gold mining in Jendi Village, Wonogiri contaminated by mercury. The methods used in this study included bacterial isolation, media preparation, phenotypic identification including; morphological and physiological tests and genotyping tests. The results showed that the bacterial isolate A3 grew optimally in media with the addition of 10% NaCl, at a temperature of 27°C, and pH 9. There were negative reactions to the observations of gram staining, acid production from glucose, indole production, catalase and urease, and positive reactions to oxidation. A neighbor-joining phylogenetic tree based on the 16S rRNA gene sequence showed that the A3 strain was closely related to Sphingosinicella microcystinivorans strain Y2T (JCM 13185T) with 100% Query coverage and a maximum identity of 99.56%.
Keywords: Gold-mining, Mercury, Sphingosinicella sp. PCR.